Double-Sided Graphene-Enhanced Raman Scattering and Fluorescence Quenching in Hybrid Biological Structures - Sarau, George; Daniel, Christoph; Heilmann, Martin; Leuchs, Gerd; Amann, Kerstin Ute; Christiansen, Silke H. (Advanced Materials Technologies, 2021)
Due to their large contact and loading surfaces as well as high sensitivities to chemical changes, graphene-based materials (GBMs) are increasingly being employed into novel nanomedicine technologies. Here biomolecule-monolayer graphene-kidney tissue hybrid structures are studied using mapping micro-Raman and fluorescence spectroscopies. Because in this configuration graphene interacts with molecules on both sides, a double-sided graphene-enhanced Raman scattering (GERS) effect up to approximate to 10.1 is found for biomolecules adsorbed on graphene and amino acids in the kidney tissue below graphene. Moreover, graphene causes an efficient autofluorescence quenching (FLQ) up to approximate to 20% emitted by the kidney tissue. Despite the complexity of such layered materials, the intriguing simultaneous occurrence of double-sided GERS (a new development of GERS) and FLQ phenomena can be well explained by suitable molecular structure and energy level alignment between molecules and graphene. These result in effective charge transfer mediated by non-covalent interactions as indicated by correlative strain, doping, and defect analyses in graphene based on the Raman data and energy level calculations. Last, the advantages of using graphene over standard photobleaching are demonstrated. This work can be extended to other macromolecular entities toward integrating GBMs in versatile drug delivery, imaging, and sensing devices.
CRIS-Team WoS Importer:2021-08-13